Genealogi pendidikan entrepreneurship dalam Islam - Sarwadi; Kharis Syuhud Mujahada; Hanifah Noviandari (At Turots: Jurnal Pendidikan Islam, 2021)
The foundation of Islamic education as the basis of Islamic education is the Qur'an, Al Hadith of the Prophet Sholallahu alaihi wasalam. Islamic education in the course of its history is rife with various kinds of ideology that have an impact on the quality of the generation produced. Islam as a plenary religion has actually given an ideological message that the nature of man is a servant while carrying out the mandate of managing, elaborating and optimizing all the potentials of nature and humans. Entrepreneurship, education and economics eventually became an integral link to answer the message of the Caliph facing an educational challenge in the era of disruption. Therefore, it becomes important to be studied in depth related to the genealogy of entrepreneurship education. The purpose of doing this genealogy study is to find out the genealogy of entrepreneurship in the Islamic world specifically the results of research based on a literature review found that entrepreneurship activities had been encountered since the time of the prophet Adam Alaihi as Salam The oldest and most survive entrepreneur activity of all time is agroopreneurship.